Assessment and quantification of ipsilateral and contralateral ankle joint alignment changes after unilateral total knee arthroplasty for knee osteoarthritis with varus deformity: a retrospective cohort study - Ahmed A. Khalifa; Amr A. Fadle; Abdelrahman A. Aziz Khalaf; Ahmed M. Abdelaal; Mohamed M. A. Moustafa (Knee Surgery & Related Research)
Abstract Purpose The study’s primary objective was to assess and quantify the ipsilateral (side A) and contralateral (side B) ankle joint line orientation (AJLO) changes after unilateral total knee arthroplasty (TKA) for primary knee osteoarthritis (OA) with varus deformity. The secondary objectives were to detect if there was a correlation between the knee deformity correction and AJLO changes and if the knee and ankle clinical outcomes on the TKA side correlate with joint alignment changes. Methods This retrospective cohort study included 70 patients with a mean age of 61.76 ± 5.96 years. The lower limb alignment was evaluated using the hip-knee-ankle (HKA) angle, while the AJLO was assessed using the tibial plafond to horizontal line angle (TPHA). The functional outcomes for side A were evaluated at a median follow-up of 18 (interquartile range (IQR): 12–46.2) months using the Knee Injury and Osteoarthritis Outcome Score (KOOS) and The American Orthopaedic Foot and Ankle Society (AOFAS) score for the knee and ankle joints, respectively. Results In side A, the HKA significantly improved from 167.49 ± 6.25 to 177.08 ± 4.39 (p < 0.001). No difference in AJLO was found between both sides preoperatively (p = 0.329). At the last follow-up, in side A, the AJLO changed significantly into less varus from −7.11 ± 5.44° to −1.10 ± 4.91° (p < 0.001); in side B, the AJLO showed no significant changes (−6.38 ± 6.10° versus −6.65 ± 6.50°, p = 0.970). For side A, the KOOS and AOFAS showed significant improvement, 45.20 ± 14.94 versus 75.72 ± 13.28 (p < 0.001) and 70 (65–75) versus 90 (80–90; p < 0.001), respectively. The preoperative HKA and AJLO on side A and side B showed significant positive correlations (r = 0.591, p < 0.001 and r = 0.611, p < 0.001, respectively). On side A, the postoperative HKA and AJLO showed a significant positive correlation (r = 0.298, p = 0.012). The preoperative and postoperative AJLO and AOFAS on side A showed nonsignificant negative correlations (r = −0.202, p = 0.277 and r = −0.115, p = 0.537, respectively). The preoperative and postoperative HKA and AOFAS on side A showed nonsignificant positive correlations (r = 0.126, p = 0.499 and r = 0.331, p = 0.069, respectively). The linear regression analysis indicated that for every 1° correction in HKA, the AJLO changed by 0.5° (R 2 = 0.241, 95% confidence interval (CI) 0.298–0.747, p < 0.001). Conclusions The ipsilateral ankle joint realigned to a less varus position after ipsilateral TKA for managing knee OA with varus deformity, with an estimated half a degree of less varus AJLO after HKA correction by a degree. No changes occurred in the contralateral ankle joint. The ankle joint function improvement was not correlated to the HKA or AJLO changes.